Sorption Behaviour of Atrazine onto Natural Sediments under Various Solution Conditions - Qing-H. Tao; Hong-X. Tang (Adsorption Science & Technology, 2004)
Potentiometric titrations, XRD analysis and batch adsorption experiments were conducted under various solution chemistry conditions to study the uptake of atrazine (AT) from sediment/water suspensions. A constant capacitance surface complexation model was then applied to interpret the reaction mechanism at the aqueous sediment surfaces. The results obtained showed that the sediment sample was negatively charged over a large range of pH values, with the model calculations matching well with the experimental results. Increasing pH value and low ionic strength, as well as high solid concentrations, led to a decrease in the adsorption of AT. The existence of dissolved organic matter (DOM) in the sediment/water system also influenced the uptake of AT by the sediment. A large increase in AT adsorption occurred for sediment pre-incubated with DOM, with a decrease in AT uptake occurring when herbicide was pre-incubated with DOM. In addition, the results suggested that long aliphatic chains must play an important role in the pesticide interaction with DOM fractions.